Determinasi Penyerapan Tenaga Kerja Usaha Mikro Kecil Menengah Studi Kasus: Kabupaten Aceh Barat - Ilfan Sahwi; Yayuk Eko Wahyuningsih; Noval Suhendra; Leli Putri Ansari; Okta Rabiana Risma (Jurnal Ilmiah Ekonomi Terpadu (Jimetera), 2025)
This study aims to examine determinants such as economic growth and district/city minimum wages on labor absorption in the MSME sector in West Aceh Regency. The selection of MSMEs is based on their important contribution to regional and national economic development, especially through job creation and income equality. This study uses multiple linear regression analysis methods using secondary data from 2000-2024. Empirical results show that economic growth and minimum wages statistically have a positive and significant effect on labor absorption, both partially and simultaneously. The regression model meets all the criteria of classical assumptions and produces an adjusted R² value of 0.749, indicating that around 74.9% of the variability in labor absorption can be attributed to the two independent variables. These results underscore the need for a regional-based economic strategy that emphasizes sustainable growth and well-calibrated wage policies to encourage a healthy entrepreneurial environment and long-term labor market development in the MSME sector.